4 luni, 3 saptamâni si 2 zile [videorecording (DVD)] = 4 months, 3 weeks, and 2 days - Mungiu, Cristian, 1968-; Marinca, Anamaria; Vasiliu, Laura (Genius Products, 2008)
1987, Communist Romania. During the course of one day, Otilia helps her friend and roommate Gabita get a late-term abortion. With abortion, let alone any kind of contraceptive, being illegal, the girls have to use illegal means to achieve their goal. Shows the rough and gritty situation in which the girls, particularly Otilia, must make decisions and deal with their consequences.